Pengaruh kepemimpinan kepala sekolah, keaktifan komite sekolah, dan iklim sekolah terhadap kinerja guru SMP negeri di Kecamatan Magelang Utara Kota Magelang - Budi Wardoyo; Samidjo Samidjo (Universitas Sarjanawiyata Tamansiswa, 2015)
The aim of this research is to determine how far the principal’s leadership, school committee’s activity, and school’s climate influence teachers’ performance of Public Junior High School in North Magelang Subdistrict Magelang City, simultaneously and partially. Furthermore, this research also analyzes the moderating role of Department of Education on the influence of these three variables on the teachers’ performance. The population of this research was 260 teachers. Sample size determined using Isaac and Michael’s method amounting to 149 teachers. The sample was determined by Proportionate Random Sampling technique. Research data were collected through questionnaires and analyzed using multiple regression statistical formulas and partial correlation. To determine the influence of independent variables on the dependent variable was done by using the F-test at a significance level of 5%. The statistical analysis showed that the variables of principal’s leadership, the school committee’s activity, and school’s climate have a positive influence on the teachers’ performance with effective contribution 62,5%. This figure shows that 62.5% of teachers’ performance is determined by the three variables, while the remaining 37.5% is determined by other variables outside of the model. Partially the principal’s leadership variables contribute effectively (SE) of 14.92%, the school committee’s activity is 14.42%, and the school’s climate is 33.16% in determining the teachers’ performance. Furthermore, based on the Chow-Test results, it is concluded that the role of the Education Department of Magelang moderates the influence of these three factors on the teachers’ performance.